Perancangan Sistem Informasi Penjualan Kosmetik pada Toko Beauty Cosmetic - Refi Difa Arcelia; Indrawan Ady Saputro (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Advances in information technology have become a major influence on society in meeting needs, quality and convenience. One example of technological progress is online sales. E-commerce or online shops can make it easier for people to shop with time efficiency, accuracy and quality and can make it easier for the shop to sell because it can promote the products it sells more widely and get maximum profits. This research focuses on designing the UI/UX for cosmetic sales at beauty cosmetic stores. Researchers found problems in beauty cosmetic stores in that store management was still manual, only using social media as promotion without an online sales platform so that the income obtained from sales was not optimal. The method used in designing the UI/UX for selling cosmetics at this beauty cosmetic shop is using the prototype method. The results of this research are the UI/UX design for selling cosmetics at beauty cosmetic shops which can make it easier for beauty cosmetic shops to market their products. It is hoped that this learning media can increase people's interest in shopping at beauty cosmetic stores.